2014
DOI: 10.1051/0004-6361/201322303
|View full text |Cite
|
Sign up to set email alerts
|

Spectral formation in a radiative shock: application to anomalous X-ray pulsars and soft gamma-ray repeaters

Abstract: Context. In the fallback disk model for the persistent emission of anomalous X-ray pulsars (AXPs) and soft gamma-ray repeaters (SGRs), the hard X-ray emission arises from bulk-and thermal Comptonization of bremsstrahlung photons, which are generated in the accretion column. The relatively low X-ray luminosity of these sources implies a moderate transverse optical depth to electron scattering, with photons executing a small number of shock crossings before escaping sideways. Aims. We explore the range of spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 35 publications
(42 reference statements)
10
21
0
Order By: Relevance
“…In addition, our current observations of the HXC are limited up to ∼60 keV. The HXC cutoff is expected at ∼400 keV by the fossil disk model (Kylafis et al 2014), while the annihilation line is suggested in some magnetar models (Beloborodov 2013b). Thus, soft gamma-ray observation is expected to provide a smoking gun.…”
Section: Uniqueness Of the Two Spectral Componentsmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, our current observations of the HXC are limited up to ∼60 keV. The HXC cutoff is expected at ∼400 keV by the fossil disk model (Kylafis et al 2014), while the annihilation line is suggested in some magnetar models (Beloborodov 2013b). Thus, soft gamma-ray observation is expected to provide a smoking gun.…”
Section: Uniqueness Of the Two Spectral Componentsmentioning
confidence: 86%
“…Canonical pulsars (dot symbols), X-ray Dim Isolated Neutron Stars (XDINS; triangles), and Rotating RAdio Transient (RRAT; inverted triangles) are shown for comparison. (Trümper et al 2010(Trümper et al , 2013Kylafis et al 2014).…”
Section: Uniqueness Of the Two Spectral Componentsmentioning
confidence: 99%
“…The slope of the power law and the energy of the cutoff depend on the energy of the seed photons, the temperature of the electrons, the velocity of the accretion flow, and the optical depth in the accretion column, which determines the number of scatterings that a photon will undergo before emerging (e.g. BW07; Kylafis et al 2014). …”
Section: Description Of the Physical Modelmentioning
confidence: 99%
“…The spectral model required to fit the data corresponds to the following physical picture (first discussed in Trümper et al 2010Trümper et al , 2013Kylafis et al 2014): photons produced in the accretion flow are up-scattered by the thermal as well as the bulk-motion Comptonization mechanisms by the infalling electrons. These upscattered photons comprise the power-law component of the observed spectrum.…”
Section: Description Of the Physical Modelmentioning
confidence: 99%
See 1 more Smart Citation